Penghindaran Pajak Dan Pencegahannya - Santy Fitnawati WN; Nuradia Fitria; Arif Rahman (LP3M INSTITUT KH YAZID KARIMULLAH, 2024)
Tax avoidance has become a global issue that is widely discussed in various countries in the world. Every year there is an estimated state loss of around Rp 69 trillion due to tax avoidance schemes in Indonesia. This research method uses a qualitative method, while the data collection technique is done by searching from various sources, be it through print or electronic mass media coverage. The results show that there are obstacles in the formulation of anti-tax avoidance rules in Indonesia, where the government is faced with taxpayers who are able to take advantage of existing tax provisions. In this regard, the government has attempted to prevent tax avoidance through the implementation of policies such as anti thin capitalization, CFC rule, transfer pricing, and anti treaty shopping. However, policies that fall into the SAAR category are considered not optimal. Therefore, the government can also consider GAAR instruments that are currently applied in various countries.